(untitled) (Fiep Bulletin - online, 2014)
Introduction: Currently there has been a growing number of obese people in the world and consequently the diseases associated with obesity has also increased such as High Blood Pressure, Coronary Heart Diseases and Diabetics Type 2 (DT2) which are among the most well-known ones. In the treatment of DT2, utilization of physical exercises were carried-out, besides the controlling of the glicemic and re-education of nutrition. The objective of this study was to verify how (mg/dl) would be the alterations in the capillary glucose after a session of aerobic exercises in of diabetics of Type 2. Methodology: It was a field and quantitative study presented in a transversal drawing. The population study was composed of participants from the Association of Diabetics of the State of Tocantins (ADSTO), patients were indicated by a doctor and also a pharmacist. The sample was intentionally selected, eleven (11) individuals participated in the sample being of both sexes ( 4 females and 7 males) in the age group of 39 to 71, the height and corporal mass were measured according to Gordon et al (1988), the Body Mass Index was obtained base on the orientations of Keys et al (1972) and in the interpretation of the BMI, the table proposed by the Center Disease Control and Prevention was used (2007). Results: The level of the capillary glucose that diminished was of an average of (mg/dl) 57.27 d 28.91 after an aerobic exercise session. The diabetics who affirmed that they practiced physical exercises regularly presented the glicemic before the exercises to be lower than those who did not practice physical exercises. The BMI (kg/m2) of the diabetics were classified as overweighed, on the threshold of obesity.